1996
DOI: 10.24310/abm.v21i0.8665
|View full text |Cite
|
Sign up to set email alerts
|

Patrones de distribución en la flora liquénica xerófila del Sureste de España

Abstract: Se hace un análisis fitogeográfico de la flora liquénica de zonas subáridas del sureste de España, la más seca de Europa. Se han distinguido los patrones de distribución siguientes: Xerotérmico-Pangeico, Circumtético, Mesogeo, Mediterráneo, Oeste Mediterráneo-Macaronésico, Iberoafricano, Mediterráneo-Sudafricano. 6 taxones son, según los datos que disponemos en la actualidad, endémicos del área considerada. Se comenta la posible diferenciación geográfica e histórica de cada elemento y se presentan mapas de dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
2

Year Published

1998
1998
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 7 publications
0
8
0
2
Order By: Relevance
“…Plant species that show an extreme East-West disjunction in the Mediterranean region have been noticed for a long time (Engler, 1879;Willkomm, 1896;Braun-Blanquet & Bolòs, 1957;Davis & Hedge, 1971). More recently, also some examples of disjunctly distributed lichens were reported in the literature (Barreno, 1991;Egea & Alonso, 1996). Additional striking examples come from studies of cave-dwelling Crustaceae (Brehm, 1947), freshwater zooplankton (Miracle, 1982), Coleoptera (Sanmartin, 2003) and from a detailed survey of the insect fauna of the central Monegros region of Spain which listed 62 species showing a disjunct distribution between NE Spain and the steppes in the eastern Mediterranean area or Central Asia (Ribera & Blasco-Zumeta, 1998).…”
Section: Introductionmentioning
confidence: 93%
“…Plant species that show an extreme East-West disjunction in the Mediterranean region have been noticed for a long time (Engler, 1879;Willkomm, 1896;Braun-Blanquet & Bolòs, 1957;Davis & Hedge, 1971). More recently, also some examples of disjunctly distributed lichens were reported in the literature (Barreno, 1991;Egea & Alonso, 1996). Additional striking examples come from studies of cave-dwelling Crustaceae (Brehm, 1947), freshwater zooplankton (Miracle, 1982), Coleoptera (Sanmartin, 2003) and from a detailed survey of the insect fauna of the central Monegros region of Spain which listed 62 species showing a disjunct distribution between NE Spain and the steppes in the eastern Mediterranean area or Central Asia (Ribera & Blasco-Zumeta, 1998).…”
Section: Introductionmentioning
confidence: 93%
“…The short‐distance seed dispersal of gypsophiles is responsible for the high number of very narrow endemisms typical of gypsum outcrops (Escudero et al , 2000 b ; Mota et al , ) and suggests that gypsum species are evolutionarily old taxa due to the long time they need to colonize isolated outcrops by chance (Moore & Jansen, ). Consequently, several authors have suggested that some Iberian gypsophiles (including plants as well as lichens and bryophytes) have a pre‐Pleistocene origin with disjoint distributions between the west/east Mediterranean and central Asian regions (Braun‐Blanquet & Bolòs, ; Barreno, ; Egea & Alonso, ). Interestingly, there seems to be a perfect match between the distribution of some insects and their host gypsophiles in these areas which are nowadays disconnected (Ribera & Blasco‐Zumeta, ).…”
Section: Evolution and Biogeography Of Gypsophilesmentioning
confidence: 99%
“…Lumbsch. (= steppicus ), steppe species distributed in the central Ebro valley, the Negev desert, and areas with gypsum soils in Crimea and other Caspian republics, a pattern found among several Mediterranean − Turanian gypsiferous species (Llimona, 1973; Egea & Alonso, 1996; J. Etayo, unpublished data). There are other numerous examples of biogeographical links between the flora of NW Africa (some species extending their distribution to the Iberian Peninsula) with SW and central Asia, and the favoured explanation is that present populations (of the same or related vicariant species) are the remnants of former continuous distributions across the central and southern Palaearctic region during most of the Late Tertiary (Davis & Hedge, 1971).…”
Section: Introductionmentioning
confidence: 99%
“…The pre‐Pleistocene origin of at least some of the disjunct distributions of plants is now generally accepted (e.g. Braun‐Blanquet & BoloÂs et al ., 1957; Davis & Hedge, 1971; Thorne, 1972; Willis, 1996; or Barreno, 1991 and Egea & Alonso, 1996 for bryophytes and lichens), but the examples of animal species are more controversial, with many still unresolved biogeographical links between the fauna of the Iberian Peninsula, north Africa, the eastern Mediterranean, and Asia (see, e.g. López Martínez, 1989).…”
Section: Introductionmentioning
confidence: 99%